Acute Care Surgery Handbook : Volume 1 General Aspects, Non-gastrointestinal and Critical Care Emergencies - Di Saverio, Salomone; Catena, Fausto; Ansaloni, Luca; Coccolini, Federico; Velmahos, George (Springer International Publishing : Imprint: Springer, 2017)
This pocket manual is a practically oriented, wide-ranging guide to acute care surgery general aspects and to non-gastrointestinal emergencies. It covers the most common problems in thoracic, obstetric, gynecologic, anorectal, vascular and skin surgery and also includes chapters on postoperative complications in bariatric surgery, antibiotic management, nutrition and interventional radiology in acute care surgery. This guide stems from collaboration with the World Society of Emergency Surgery (WSES) and aims to provide general surgeons, residents and trainees with a comprehensive and up-to-date overview of the most relevant operative techniques and with useful "tips and tricks" applicable in daily clinical practice. A second volume on gastrointestinal and abdominal surgical emergencies is also available.- Resumé vydavatel
Keywords: urgentní medicína; intenzivní medicína; traumatologie; chirurgie; emergency medicine; critical care medicine; traumatology; surgery; elektronické knihy; příručky; electronic books; handbooks and manuals